Transcription factor requirements for in vitro formation of transcriptionally competent 5S rRNA gene chromatin. - Felts, S J (1990)
The Saccharomyces cerevisiae 5S rRNA gene was used as a model system to study the requirements for assembling transcriptionally active chromatin in vitro with purified components. When a plasmid containing yeast 5S rDNA was assembled into chromatin with purified core histones, the gene was inaccessible to the yeast class III gene transcription machinery. Preformation of a 5S rRNA gene-TFIIIA complex was not sufficient for the formation of active chromatin in this in vitro system. Instead, a complete transcription factor complex consisting of TFIIIA, TFIIIB, and TFIIIC needed to be formed before the addition of histones in order for the 5S chromatin to subsequently be transcribed by RNA polymerase III. Various 5S rRNA maxigenes were constructed and used for chromatin assembly studies. In vitro transcription from these assembled 5S maxigenes revealed that RNA polymerase III was readily able to transcribe through one, two, or four nucleosomes. However, we found that RNA polymerase III was not able to efficiently transcribe a chromatin template containing a more extended array of nucleosomes. In vivo expression experiments indicated that all in vitro-constructed maxigenes were transcriptionally competent. Analyses of protein-DNA interactions formed on these maxigenes in vivo by indirect end labeling indicated that there are extensive interactions throughout the length of these maxigenes. The patterns of protein-DNA interactions formed on these genes are consistent with these DNAs being assembled into extensive nucleosomal arrays.